Therapeutic benefits of nanoparticles in stroke - Panagiotou, Stavros; Saha, Sikha (Frontiers in Neuroscience, 2015)
Stroke represents one of the major causes of death and disability worldwide, for which no effective treatments are available. The thrombolytic drug alteplase (tissue plasminogen activator or tPA) is the only treatment for acute ischemic stroke but its use is limited by several factors including short therapeutic window, selective efficacy and subsequent haemorrhagic complications. Numerous preclinical studies have reported very promising results using neuroprotective agents but they have failed at clinical trials because of either safety issues or lack of efficacy. The delivery of many potentially therapeutic neuroprotectants and diagnostic compounds to the brain is restricted by the blood-brain barrier (BBB). Nanoparticles (NPs), which can readily cross the BBB without compromising its integrity, have immense applications in the treatment of ischemic stroke. In this review, potential uses of NPs will be summarized for the treatment of ischemic stroke. Additionally, an overview of targeted NPs will be provided, which could be used in the diagnosis of stroke. Finally, the potential limitations of using NPs in medical applications will be mentioned. Since the use of NPs in stroke therapy is now emerging and is still in development, this review is far from comprehensive or conclusive. Instead, examples of NPs and their current use will be provided, as well as the potentials of NPs in an effort to meet the high demand of new therapies in stroke.